Keterampilan Dasar Mengajar Mahasiswa Program Studi PGMI IAIN Samarinda: Studi pada Mahasiswa yang Mengajar di Sekolah Dasar dan Madrasah Ibtidaiyah Samarinda - Kadir, Marniati; Rukiyah, Ity (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
The research is about basic skills of teaching of Islamic Elementary School Teacher Education (PGMI) Department of Samarinda. The research objective is to describe the ability of basic skills of teaching of PGMI students who have taught at elementary school and Islamic Elementary School of Samarinda in academic year 2017-2018. The skills include the skill of opening and closing the lesson, explaining, giving affirmation, having variation, asking and organizing the class. The research method is a descriptive method. The data collection technique is using the methods of observation, interview, and documentation. Then, the data is analyzed descriptively through percentage and the ideal average of each component of the basic skills of teaching. Based on the research result, it can be concluded that the ability of basic skills of teaching are on a good criteria, they are: the skill of opening and closing the lesson (the average score is 26,25 or 72,91%), affirmation skill (the average score is 19,52 or 69,91%), asking skill (the average score is 17,75 or 73,95%), and the skill of organizing the class (the average score is 26,50 or 73,61%), and there are two skills in the category of enough, they are explaining skill (the average score is 17,37 or 62,03%) and having variation skill (the average score is 17,00 or 60,70%). Next is needed a more comprehensive study related to the students’ skill at the department of PGMI, so that the information and the findings will be a consideration in the efforts of increasing the students competency of PGMI department of IAIN Samarinda.